Eksistensi Kuliner Kabuyutan Garut dalam Konteks Wisata Gastronomi Jawa Barat - Darwis, Riadi (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2025)
West Java is renowned for its rich culinary heritage, which significantly contributes to the creative economy and offers potential for gastronomic tourism. This research focuses on the culinary traditions at the Garut kabuyutan site, examining aspects such as the position, types, processing, consumption timing, serving methods, utensils, and etiquette during traditional events. The study employs descriptive methods, utilizing observation, documentation, and interviews, and analyzes the data through reduction, presentation, and conclusion drawing. Culinary offerings at these events are grouped into three categories, with 562 types identified across 20 categories in 12 curated Garut kabuyutan. Food is typically served at the center of the event space, using traditional containers and banana leaves. Preparations often begin at least a month in advance, and meals are usually served between noon and sunset. Traditional utensils remain the preferred choice. Etiquette is emphasized, including neat and attractive packaging, proper display, the recitation of prayers, specific seating arrangements, and a defined order for who eats first. These practices highlight the cultural significance and communal values embedded in West Java’s culinary traditions, supporting both cultural preservation and economic development through gastronomy